Investigating The Students' Reading Difficulties in Understanding English Text - Nurul Annisa; Ummi Khaerati Syam; Andi Bulkis Maghfirah Mannong (English Language Teaching Methodology, 2023)
The purpose of this study is to identify the difficulties faced by the eighth-grade students of SMP Negeri 3 CAMBA, as well as the factors causing the students' problems understanding English reading text. This study is qualitative. The eighth-grade students of SMP Negeri 3 CAMBA were the research subjects. The data collection methods are interviews and tests. The researcher presents the data from the difficulties in understanding English reading text. The result of the research shows that there are 26.31% of students have difficulties understanding to look for the main idea of the text. Then, there are 12.86% of students have difficulties understanding the vocabulary of the text. Then, there are 8.77% of students have difficulties in understanding and making inferences from the text. Next, there are 52.04% of students have difficulties understanding to look for the detailed information in the text. The factor causing the students difficulties found in comprehending English reading text there is difficulty in understanding the meaning of words, difficulty in determining the main idea, difficulties in understanding a long sentence in the text, difficulty in understanding vocabulary, house environment, and school environment.